Production of rhamnolipid biosurfactant by Pseudomonas aeruginosa using sludge palm oil as carbon source in stirred tank bioreactor - Yaacob, Nadhirah (2019)
Rhamnolipid biosurfactant is a lipid surfactant produced from various carbon sources through fermentation by many species of Pseudomonas and Acinetobacter. The importance of rhamnolipid biosurfactant is focused on the role of oil recovery in oil and gas industry. Rhamnolipid biosurfactant is an amphipathic structure and has various and unique carbon chain (lipid). Rhamnolipid biosurfactant production is costly due to high cost of fermentation, recovery and purification process. Reduced fermentation cost for rhamnolipid biosurfactant production may be achieved using waste such as sludge palm oil (SPO) as carbon sources, which is abundantly produced by palm oil industry. The possibility of using SPO as carbon source in fermentation by Pseudomonas aeruginosa for rhamnolipid production was investigated in this study. The pure strain of P. aeruginosa (ATCC 9027) was obtained from Advanced Oleochemical Technology (AOTD), Malaysian Palm Oil Board (MPOB), which was initially purchased from AXON Scientific Sdn. Bhd. Preliminary, the selection of appropriate basal medium for rhamnolipid production by P. aeruginosa was carried out in shake flask culture. The effect of SPO, glucose and sodium nitrate concentrations was also investigated in shake flask culture using the selected basal medium. The effect of culture’s pH, agitation speed and aeration rate was evaluated in 1.3 L stirred tank bioreactor using the optimal medium obtained from shake flask study. The effect of dissolved oxygen transfer (DOT) on rhamnolipid production was also evaluated in 1.3 L stirred tank bioreactor. The extraction of Rhamnolipid produced by fermentation in stirred tank bioreactor using SPO as carbon source was performed using acid precipitation and solvent extraction methods. Rhamnolipid was purified using TLC and HPLC methods. The LCMS analysis was carried out on the purified rhamnolipid in order to propose the structures. From shake flask experiments, the optimal medium for rhamnolipid production by P. aeruginosa (ATCC 9027) was achieved using 16 g/L glucose, 0.2 g/L NaNO3 and with the addition of 0.2% v/v SPO which produced 14 g/L rhamnolipid. The rhamnolipid production using the optimal medium was 2 times higher as compared to non-optimal medium. In fermentation using stirred tank bioreactor, the optimal cultivation conditions were achieved at initial culture pH 5, temperature of 30°C, agitation speed of 400 rpm and air flow rate at 0.2 vvm, in which the dissolved oxygen tension (DOT) was controlled at 90% saturation throughout the fermentation The maximum rhamnolipid concentration obtained under this optimal fermentation condition was 14.79 g/L, which gave the cell efficiency and overall rhamnolipid productivity of 0.736 g/L and 0.287 g/Lh respectively. The HPLC chromatogram of rhamnolipid produced by P. aeruginosa (ATCC 9027) through the fermentation using SPO has four peaks, indicated that different fatty acid chains of mono rhamnolipid and di-rhamnolipid were presence. The analysis of the peaks using liquid chromatography mass spectrophotometer (microOTOF-Q) indicated that peak 1 has m/z value of 649.3824, peak 2 with m/z value of 675.3934, peak 3 has 503.3235 m/z value and peak 4 has value m/z of 677.4108, in which, structure of rhamnolipid biosurfactant for each peak was proposed. Results from this study demonstrated that SPO could be used as the promising raw materials for rhamnolipid production at reduced cost.